Incubation of Immune Cell Grafts With MAX.16H5 IgG1 Anti-Human CD4 Antibody Prolonged Survival After Hematopoietic Stem Cell Transplantation in a Mouse Model for Fms Like Tyrosine Kinase 3 Positive Acute Myeloid Leukemia - Hilger, Nadja; Mueller, Claudia; Stahl, Lilly; Mueller, Anne M.; Zoennchen, Bianca; Dluczek, Sarah; Halbich, Christoph; Wickenhauser, Claudia; Gerloff, Dennis; Wurm, Alexander A.; Behre, Gerhard; Kretschmer, Anna; et al. (Frontiers in Immunology, 2018)
Despite the constant development of innovative therapeutic options for hematological malignancies, the gold-standard therapy regimen for curative treatment often includes allogeneic hematopoietic stem cell transplantation (HSCT). The graft-vs.-leukemia effect (GVL) is one of the main therapeutic goals that arises from HSCT. On the other hand, graft-vs.-host disease (GVHD) is still one of the main and most serious complications following allogeneic HSCT. In acute myeloid leukemia (AML), HSCT together with high-dose chemotherapy is used as a treatment option. An aggressive progression of the disease, a decreased response to treatment, and a poor prognosis are connected to internal tandem duplication (ITD) mutations in the Fms like tyrosine kinase 3 (FLT3) gene, which affects around 30% of AML patients. In this study, C3H/HeN mice received an allogeneic graft together with 32D-FLT3ITD AML cells to induce acute GVHD and GVL. It was examined if pre-incubation of the graft with the anti-human cluster of differentiation (CD) 4 antibody MAX.16H5 IgG1 prevented the development of GVHD and whether the graft function was impaired. Animals receiving grafts pre-incubated with the antibody together with FLT3ITD AML cells survived significantly longer than mice receiving untreated grafts. The observed prolonged survival due to MAX.16H5 incubation of immune cell grafts prior to transplantation may allow an extended application of additional targeted strategies in the treatment of AML.